2021
DOI: 10.1002/jmv.26883
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 infection affects the lower urinary tract and male genital system: A systematic review

Abstract: PubMed, Scopus, and ISI Web of Knowledge databases were searched to identify studies published up to December 2020 on the involvement of urinary and male genital systems in COVID-19. Sixteen studies involving a total of 575 patients (538 males and 37 females) were included in this systematic review.The COVID-19 phase was available for 479 patients: 426 in the acute and 53 in the recovery phase. De novo lower urinary tract symptoms (LUTS) were observed in 43 patients and deterioration of pre-existing LUTS in 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 40 publications
1
44
0
1
Order By: Relevance
“…In a systematic review of 16 studies including a total of 575 patients, 43 patients reported lower urinary tract symptoms at the onset of the disease, and 7 patients had worsening of previous symptoms. Scrotal discomfort and swelling, pain and redness, low flow priapism, bladder bleeding, and acute urinary retention were the urological disorders (22). Urological complaints questioned in our study group were rarely reported among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 60%
“…In a systematic review of 16 studies including a total of 575 patients, 43 patients reported lower urinary tract symptoms at the onset of the disease, and 7 patients had worsening of previous symptoms. Scrotal discomfort and swelling, pain and redness, low flow priapism, bladder bleeding, and acute urinary retention were the urological disorders (22). Urological complaints questioned in our study group were rarely reported among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 60%
“…Although less-identified, but becoming increasingly reported, are patients with COVID-19 developing new onset or an exacerbation of baseline urinary symptoms, most notably overactive bladder (OAB) [ 3 , 4 ]. This has been referred to as COVID-19-associated cystitis (CAC) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 remain asymptomatic in 60-70% of cases, while the remaining 30-40% became symptomatic after an average incubation of 5-6 days, length differing from a subject to another mainly according to age and intensity the immune reaction. The most frequent clinical symptoms are fever (89%), cough (68%), fatigue (35%), sputum production (30%), shortness of breath (15%); headaches, weakness, sore throat, and gastrointestinal disorders (nausea, vomiting, diarrhea); pleural pain occur in 10-15% of cases [15][16][17][18][19][20][21][22]. Abnormalities at the computerized tomography (CT) scanning are observed in 86.2% of pneumonia cases, the more common pattern being frosted glass opacities and an irregular bilateral shading.…”
Section: Introductionmentioning
confidence: 99%